2016
DOI: 10.1016/j.jssc.2015.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of single crystals of transition metal vanadates in the glaserite phase

Abstract: A series of transition metal vanadate crystals were prepared using a high temperature (580 ˚C) hydrothermal method. The compounds all had the general formula A 2 AEM(VO 4) 2 (A = K, Na, Li; AE = Ba, Sr; M = Co, Fe, Mn). They are all variations of the glaserite structural type and range in symmetry from P-3m1 to P-3 to P2 1 /c. Most of the derivatives contain a planar threefold rotation operation, making them possible spin frustration candidates. Single crystal structural analyses were performed on many of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 32 publications
(34 reference statements)
3
33
0
Order By: Relevance
“…In fact, there are still many unknown physical characteristics related to it as well as its Raman spectrum. It belongs to a wide class of structures known as glaserite phases, which compounds have been more deeply studied than the specific K 3 Na(SO 4 ) 2 . The first problem detected is related to its common name, because there are two possible terms: aphthitalite and glaserite.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are still many unknown physical characteristics related to it as well as its Raman spectrum. It belongs to a wide class of structures known as glaserite phases, which compounds have been more deeply studied than the specific K 3 Na(SO 4 ) 2 . The first problem detected is related to its common name, because there are two possible terms: aphthitalite and glaserite.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently we have been investigating tetrahedral vanadate, [VO 4 ] 3-, as an oxyanion building block in hydrothermal conditions, and found that it displays an extremely rich coordination chemistry as a structural unit for both rare earths [5] as well as d-block metal ions. [6][7][8] Vanadates are intriguing building blocks in that they are isostructural to the phosphates, which of course display an exceptionally rich and diverse coordination chemistry. However, the exploratory structural chemistry of the vanadates is not yet as fully developed as the corresponding phosphates.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are generally synthesized at relatively high temperatures using traditional solid‐state techniques, such as melts or fluxes , . Alternatively, our group found that high temperature (500–700 °C) hydrothermal synthesis leads to a wide range of unusual new transition metal vanadates, often in the form of large, high‐quality single crystals , . In addition to their new structure types, many of these materials have interesting magnetic properties.…”
Section: Introductionmentioning
confidence: 99%